(untitled) (Biological Sciences - PJSIR, 2007)
Effect of d i fferent con centrati on s of su crose and potassi um metabi sul ph i t e on th e apri cot pu l p was studi ed fortnight l y for 90 days throu gh ph ys icoch em ical and m icrobial an a l ysi s. No sign i ficant change i n total sol u bl e sol id s (TSS) of apricot pu l p was observed d ur i n g the storage. Ac i dity and n on-red uci n g sugar si gn i ficantl y (p<0.05) decreased , w h i l e pH and reduci ng su gars si gn i ficantl y (p<0.05) i ncreased d ur i n g th e storage. Sampl es wi t h added 20% sucro se an d 0.2% potassi um metab i sul ph ite, packed i n pl astic and gl ass contai ners, had negl i gi b l e m i crobi a l popul at i on , m a i ntai n ed m ax i m u m n utri ents and the best sen sory character istics d u ri n g the storage. Stora ge d u ration and treatmen t s h ad si gn i fi cant (p< 0.05) effect on pH , acid i ty, non red u ci n g su gars and total fu n gal cou nt , w h i l e on TSS (tota l sol ubl e sol i ds) an d red uci n g sugar, th e effect of treatment s was n on si gn ificant (p<0.05).